2015
DOI: 10.1177/0022042615580989
|View full text |Cite
|
Sign up to set email alerts
|

Parental Awareness of Substance Use Among Adolescents in a Junior High School Sample

Abstract: There is a lack of studies assessing parental awareness of adolescent alcohol, cigarette, and drug use in the general adolescent population. A total of 1,426 adolescents aged 14 to 16, and their parents, answered questions about adolescent substance use annually during junior high school. Sensitivity for parental report of adolescent substance use was low: 5.6% to 26% for drunkenness, 14.3% to 20.6% for cigarettes, and 4.9% to 12% for illicit drugs. Higher age and higher frequency of use were positively associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
1
14
1
Order By: Relevance
“…Similarly Yang et al (2006) came to like conclusions when studying parent-adolescent dyads regarding sexual risk, substance use, and violence. Researchers studying similar risks, such as alcohol consumption (Berge, Sundell, Öjehagen, Höglund, & Håkansson, 2015;Bogenschneider, Wu, Raffaelli, & Tsay, 1998), substance use (Jones, Ehrlich, Lejuez, & Cassidy, 2015), and sexual risk (B. Stanton, Cole, et al, 2004), reported parental underestimation of risk or a lack of knowledge or awareness about their youth's participation in risky behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly Yang et al (2006) came to like conclusions when studying parent-adolescent dyads regarding sexual risk, substance use, and violence. Researchers studying similar risks, such as alcohol consumption (Berge, Sundell, Öjehagen, Höglund, & Håkansson, 2015;Bogenschneider, Wu, Raffaelli, & Tsay, 1998), substance use (Jones, Ehrlich, Lejuez, & Cassidy, 2015), and sexual risk (B. Stanton, Cole, et al, 2004), reported parental underestimation of risk or a lack of knowledge or awareness about their youth's participation in risky behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An overview of the past literature implies that factors responsible for parents' belief about their adolescents' involvement in risky behaviors may also be factors that motivate adolescents to engage in those very behaviors (see Diagram 1 ). This may partly explain why parental underestimation is more protective than accurate awareness, given that underestimation is often associated with healthy parent-adolescent relationships, good academic performance, and high levels of adolescent religiosity ( Berge, Sundell, Ojehagen, Hoglund, & Hakansson, 2015 ; Green et al, 2011 ; Yang et al, 2006 ). Studies of Madon et al, 2003 , Madon et al, 2004 , Madon et al, 2006 are particularly relevant to this subject, being based on the assumption that parental belief about adolescents' alcohol use and adolescents' later alcohol consumption share nearly identical risk and protective factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Because parental awareness may be a protective factor for tobacco use initiation, and parents are often crucial to youth seeking cessation, high rates of parent unawareness could indicate a need for additional education or communication efforts targeted toward parents. Past studies have identified factors associated with parent unawareness of their children's risk behaviors (including cigarette use), which include youth age, sex, family composition, family communication, youth's academic performance, and frequency of risk behavior . Typically, parents are more unaware of substance use among younger youth, girls, youth with higher school performance, and youth who use substances less frequently .…”
mentioning
confidence: 99%
“…Past studies have identified factors associated with parent unawareness of their children's risk behaviors (including cigarette use), which include youth age, sex, family composition, family communication, youth's academic performance, and frequency of risk behavior . Typically, parents are more unaware of substance use among younger youth, girls, youth with higher school performance, and youth who use substances less frequently . Additionally, fathers are more unaware of youth substance use than mothers, as typically mothers receive information from observation or from their child, and fathers receive information from their partner .…”
mentioning
confidence: 99%
See 1 more Smart Citation